The effect of strategy training on Algerian learners’ use of vocabulary learning strategies - Amel BENYAHIA (Revue des Sciences Humaines, 2015)
This study investigates the effect of strategy training on learners’ use of vocabulary learning strategies in an Algerian EFL context. To achieve this aim, a training program about the use of six different vocabulary strategies was organised at L’Ecole Normale Supérieure de Constantine (ENSC). The training included three strategies necessary for the identification of new words’ meanings and three strategies dealing with the consolidation and memorization of new words after they have been learnt. Ten third year students underwent the training for a period of about two and half months, attending about 16 different sessions with a total of 23 hours and 30 minutes. A comparison of the results of the pre-test and post test (administered at the beginning and at the end of the training respectively) showed a sharp rise in students’ performance in the post-test reflected in their high scores in its different parts. In other words, the training had a positive impact on learners’ use of the strategies under study. In the light of these results, it is recommended that more attention be given to strategy training in order to enhance students’ use of the necessary strategies.